الفعالية الضد الجرثومية لبعض النباتات الطبية تجاه الأيروموناس العامل الممرض للأسماك المعزول من الكارب الشائع المستزرع - داؤد نزيه (Latakia University Journal -Biological Sciences Series, 2019)
A total of 18 aqueous, methanolic and ethanolic extracts of 6 plant species that are collected from local environments of Lattakia- Syria were screened for antibacterial activity against three species of bacterium Aeromonas pathogenic to common carp (Cyprinus carpio). The three species Aeromonas hydrophila, A. caviae and A. sobria were isolated from infected carp in freshwater fish farm located in Dam 16 Tishreen in Lattakia. It was showed that all plant extracts exhibit different degrees of activity against tested bacteria. All bacterial strains in the present study were highly sensitive to all extracts of garlic (Allium sativum (L.), thyme (Thymus vulgaris L), and onion (Allium cepa L). Moderate activity of aqueous but not alcoholic extracts of water mint (Menthe aquatic L) were observed against tested bacteria. In contrary, alcoholic extracts of eucalyptus (Eucalyptus globules) and sage (Salvia officinalis) exhibited moderate activity while the aqueous ones were weak. In general, isolates of both species A. caviae and A. sobria were more sensitive to the studied extracts when compared with A. hydrophila. Minimum inhibitory concentration (MIC) was determined for three of the studied plants. The MIC values of plant extracts against tested bacteria ranged from 1.0 to 10 mg/ml for garlic, 2.0 to 15 mg/ml for onion and 13 to 25mg/ml for thyme extracts. درست الخواص الضد جرثومية ل 18 خلاصة مائية و ميتانولية و إيتانولية تعود إلى 6 أنواع نباتية جمعت من البيئات المحلية في اللاذقية- سوريا تجاه ثلاثة أنواع لجرثوم الأيروموناس العامل الممرض لسمك الكارب الشائع. عزلت الأنواع الثلاثة للأيروموناس Aeromonas hydrophila و A. caviae و A. sobria من أسماك كارب مصابة في مزرعة سمكية مائية عذبة (سد 16 تشرين- اللاذقية). أظهرت كل الخلاصات درجات مختلفة من الفعالية تجاه الجراثيم المختبرة. كانت كل السلالات المدروسة حساسة جداً لخلاصات الثوم و الزعتر الشائع والبصل. على حين أظهرت فعالية متوسطة للخلاصات المائية للنعناع المائي تجاه الجراثيم المختبرة و لكن ليس للخلاصات الكحولية له. على العكس فإن الخلاصات الكحولية للكينا (أوكاليبتوس) و المريمية أظهرت فعالية متوسطة على حين الخلاصات المائية كانت ضعيفة الفعالية. بشكل عام, كانت سلالات النوعين A. caviae و A. sobria كليهما أكثر حساسية للخلاصات المدروسة إذا ما قيست بالنوع A. hydrophila. حدد التركيز المثبط الأصغري لثلاثة من النباتات المدروسة. راوحت قيم التركيز المثبط الأصغري للخلاصات النباتية تجاه الجراثيم المدروسة بين 1.0 و 10 ملغ/مل لخلاصات الثوم, وبين2.0 و 15 ملغ/مل لخلاصات البصل, وبين 13 و 25 ملغ/مل لخلاصات الزعتر.